ANALYSIS OF THE INFLUENCE OF LIQUIDITY, NON-PERFORMING LOANS, CAPITAL, AND TOTAL ASSETS OF BANK ON BANK PROFITABILITY BEFORE AND DURING THE COVID-19 PANDEMIC - Darwisman Darwisman; Wisnu Mawardi (Journal of Business Social and Technology, 2023)
The spread of the corona virus has had a negative impact on commercial banks in the form of reduced profitability, increased credit risk, and inefficiencies. Amid these conditions, Regional Development Banks (BPD) tend to show better profitability performance compared to private banks and commercial banks as a whole. This study aims to investigate the factors that affect BPD profitability during normal times and during the Covid-19 pandemic crisis. This study used the panel data regression analysis method of the fixed-effects model and as a support for the two sample t-test analysis. The results showed that the profitability performance of BPD as measured by the ROA variable was negatively affected by the NPL and total assets variables and positively by liquidity with the LDR proxy in normal times. The Covid-19 pandemic in general has had an impact on BPD profitability. Furthermore, the NPL and NIM variables still significantly affect the BPD ROA ratio during the Covid-19 pandemic crisis. Liquidity tends not to have a significant effect on BPD profitability during the Covid-19 pandemic and capital with a CAR proxy does not have a significant effect on BPD profitability both during normal times and during the Covid-19 pandemic